Studi Kasus Wanprestasi: Implikasi terhadap Perancangan Kontrak di Sektor Bisnis - Victor Karna Junior; Ghefari Albir Fachri Suherman; Lucky Dafira Nugroho (Pusat Riset dan Inovasi Nasional, 2025)
Default, or breach of contract, is a common problem in business transactions and can have significant impacts, both financially and non-financially. This article analyzes the various forms of default, such as failure to fulfill obligations, delays, or non-performance in accordance with the agreement. The impact of default is not only directly related to financial losses—for example through fines or damages—but can also damage business relationships and the company's reputation. Therefore, good contract design is very important in reducing this risk. Effective contract design should include clear clauses regarding obligations, deadlines, and sanctions that apply in the event of a breach. Penalty clauses are often used to provide incentives for the parties involved to fulfill their obligations. Furthermore, in the context of globalization and international transactions, it is important for contracts to include clear dispute resolution mechanisms, such as mediation or arbitration, to avoid escalation of problems. This article aims to provide practical guidance for companies in designing contracts that not only reduce the risk of default, but also ensure the sustainability of mutually beneficial business relationships. With a thorough understanding of legal risks and the implementation of appropriate mitigation measures, companies can maintain smooth operations and prevent major losses due to default. Keywords : Default, Breach Of Contract, Contract Drafting, ,, , Mediation, Arbitration, Corporate Reputation, Risk Management.